2008
DOI: 10.1111/j.1365-3180.2007.00612.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐chemical weed control on traffic islands: a comparison of the efficacy of five weed control techniques

Abstract: Summary The efficacy of five non‐chemical weed control methods for reducing weed cover on traffic islands was investigated in the growing season of 2004. Three trial sites were divided into six treatment areas which were treated with either flame, steam, hot air, hot water, brushes or left untreated. The treatments were carried out at regular intervals throughout the growing season. The percentage weed cover was measured every second week using a 75 × 75 cm quadratic frame with 100 squares. In the control area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 9 publications
0
33
0
1
Order By: Relevance
“…Applied Vegetation Science (Kristoffersen et al 2007). Additionally, perennial nonnative grasses dominating our sites are difficult to kill with steam (Wei et al 2010).…”
Section: Non-native Grassesmentioning
confidence: 99%
“…Applied Vegetation Science (Kristoffersen et al 2007). Additionally, perennial nonnative grasses dominating our sites are difficult to kill with steam (Wei et al 2010).…”
Section: Non-native Grassesmentioning
confidence: 99%
“…, 2001). In contrast, many non‐chemical methods need more frequent treatments for adequate weed control (Ascard, 1995; Rask & Kristoffersen, 2007; Kristoffersen et al. , 2008b), and their effectiveness is strongly related to weed species and growth stage at the time of treatment (Melander et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is suggested that the use of A. pintoi as cover associated with green plantain is possible to reduce the number of herbicide applications, the reduction of herbicides rates is not recommended as a mean to save on input costs but as reduced application rates helping to reduce input costs. arvenses puede incrementar la presión de las arvenses en los siguientes años, como son las anuales, que extienden sus semillas y arvenses perennes tiene una buena oportunidad para aumentar su biomasa radical o rizoma (Kristoffersen et al, 2008) con una fuerte competencia por nutrientes con el cultivo.…”
Section: Discussionunclassified
“…Qasem (1992) analyzed nutrients absorption by weeds, beans and tomatoes finding that the concentrations of N, P, K and Mg were higher in weed species than in cultivated species. For example, the high population of weeds can increase the pressure of weeds in subsequent years, as are annual, spreading their seeds and perennial weeds have a good chance to increase their root or rhizome biomass (Kristoffersen et al, 2008) with a strong competition for nutrients with the crop.…”
Section: Npk Uptake By Type Of Texturementioning
confidence: 99%